Implementasi Metode Lean Healthcare untuk Mengurangi Waktu Tunggu Pasien: Implementation of Lean Healthcare Methods to Reduce Patient Waiting Time - Arif, Yulastri; Muthmainnah, Muthmainnah; Putri, Zifriyanthi Minanda; Maisa, Esthika Ariany; Nelwati, Nelwati; Susmiati, Susmiati; Ananda, Yuanita; Sidaria, Sidaria; Murni, Dewi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Outpatient waiting time is one of the national quality indicators. Most patients visiting outpatient clinics in Indonesian hospitals complain about the long waiting time before receiving healthcare services. Over the decades, the persistent issue of long waiting times and unresolved patient dissatisfaction has led hospitals worldwide to adopt Lean Healthcare management systems. These systems focus on improving the efficiency and effectiveness of service operations by eliminating waste. Siti Rahmah Hospital is a private type-C hospital facing outpatient waiting time issues exceeding 60 minutes. This community service aims to enhance nurses' knowledge and reduce service waiting times. This community service was conducted using a quantitative approach with an experimental design, and the primary data collection technique was through questionnaires. The implementation consisted of four main stages: preparation, socialization of lean healthcare methods, identification of waiting times, and mapping types of time waste in services. Nurses' knowledge about lean healthcare management increased significantly by 56.70% after the training, as shown by a pretest score of 36.6% and a post-test score of 93.3%. The knowledge components that improved substantially included understanding the outpatient waiting time standard of less than 60 minutes, identifying time-wasting activities in services, and using electronic medical records as a lean healthcare strategy to reduce service waiting times. The lean healthcare method is effective in reducing patient waiting times in outpatient care.